Digital Transformation of UMKM: Avoiding the Trap of Illegal Online Loans Through Digital Marketing: Transformasi Digital UMKM: Menghindari Jerat Pinjaman Online Ilegal Melalui Pemasaran Digital - Pattisahusiwa, Salmah; Cahyaningtias, Adhelia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
The objective of this outreach is to enhance digital literacy among UMKM, particularly in the use of digital technology in business, and to prevent UMKM from becoming entangled in illegal online lending practices by providing safer and more transparent financing alternatives. Additionally, it seeks to understand public opinion regarding the use of online lending applications and social media as a means of business promotion. This community service activity employs a qualitative method with an exploratory approach, as it primarily aims to describe the results of a questionnaire on UMKM actors' opinions and understanding of online lending applications and digital marketing. Overall, the questionnaire results indicate that UMKM in this area have shown an increased understanding of utilizing digital technology, especially social media, to grow their businesses. In conclusion, this outreach has successfully achieved its objectives, though there remain significant concerns regarding data security and the risks associated with illegal lending.